KEMAMPUAN MENULIS TEKS ULASAN SISWA KELAS VIII SMP MUHAMMADIYAH 1 PEKANBARU - M Amin Anshori; Hakim Nursal; Elmustian ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the ability to write text reviews eighth grade students of SMP Muhammadiyah 1 Pekanbaru. The problem in this research is the students are required to determine the steps preparing the review text and compose the text review of a work he saw. Students are usually less able to explain the advantages and disadvantages of a work yag diulasnya. This happens because the students do not know the structure of the review text and how to explain the advantages and disadvantages of a work. This study aimed to describe the ability to write the text reviews the structure and elements of text language review grade students of SMP Muhammadiyah 1 Pekanbaru. This research method is descriptive method that is used to describe the data that is associated with the ability to write text reviews eighth grade students of SMP Muhammadiyah 1 Pekanbaru. The ability to write text reviews are scores or grades earned eighth grade students of SMP Muhammadiyah 1 Pekanbaru to test the ability to write text review. Text reviews written by 1 of text, each of which contains the text and structure of the language elements of the review text. The structure of the written form of orientation, descriptive, interpretations and conclusions. Elements languages written in the form of adjectives attitudes, words or complex sentences, and words descriptive words opinions or views.Key Words: Writing and Text Reviews